Strategi Project Based Learning Sebagai Alternatif Menciptakan Siswa Kreatif - Arlina Arlina; Nova Emiliya Pane; Wildan Sitorus; Mardiah Putri Jerohmi; Azra Munazah (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out how project-based learning strategies as an alternative create creative students. This research uses qualitative research methods using the type of study literature research. Where study literature is a type of research by answering existing problems by reviewing appropriate literature so that solutions to these problems can be given. The result of this research is the Project Based Learning learning model is an innovative learning model that involves project work where students work independently in constructing their learning and making it into real products. Project work contains complex tasks based on questions and problems that are very challenging and guides students to design, solve problems, make decisions, conduct investigative activities, and provide opportunities for students to work independently. PBL (Project Based Learning) learning strategy has a characteristic that the teacher poses problems that must be solved by students, which then students must design processes and frameworks to make solutions to these problems. Students must work together to find information and evaluate the results of their work so that the problem can be solved, so that students can produce products from the background of the problem. Thus, project-based learning strategies can be used as an alternative to creating creative students.